Pelatihan Penyusunan Laporan Keuangan Pada UMKM Ani Catering Wates - Qori Annisa; Ika Wulandari (Lembaga Pengembangan Kinerja Dosen, 2023)
Financial report preparation training held at UMKM Ani Catering is carried out in a community service program. The owner of the Ani Catering business does not have the ability to manage financial reports, but tries to advance and develop his business. The financial reports made in this training are still simple, the goal is to be easy to understand and easy to implement. The financial statements to be prepared include balance sheets, income statements and cash flow statements. With these financial reports, business owners know that the business they are running is profit or loss, and can separate their personal finances from their business finances.